Comparison of SCORE and SCORE 2 risk prediction tools in contemporary very high risk european population. (3rd October 2022) - Boskovic, N; Giga, V; Djordjevic-Dikic, A; Beleslin, B; Stojkovic, S; Nedeljkovic, I; Aleksandric, S; Tesic, M; Dedic, S; Burazor, I; Karadzic, T; Paunovic, I; et al.
Abstract: Background: New SCORE 2 algorithm overperformed SCORE algorithm in population with decreasing prevalence of cardiovascular (CV) morbidity and mortality. However, there is limited data in risk stratification with SCORE 2 model in contemporary populations from very high risk countries. Aim: The aim of this study was to compare risk prediction using SCORE 2 and SCORE model and to compare the proportions of patients requiring statin treatment in primary prevention. Methods: Our study included 1317 patients (511, 38.8% male gender, average age 54±8) without known CV disease aged 40 to 70 years. Data on CV risk factors were prospectively collected in 20 primary care centers throughout the Serbia from January 2020. to December 2020. Based on the CV risk profile, patients were stratified into 4 categories: low, moderate, high and very high risk according to SCORE model and into 3 categories: low to moderate, high and very high risk according to SCORE 2 model. The number of patients requiring statin treatment was assessed according to the risk category and value of LDL cholesterol in SCORE model and the value of non-HDL cholesterol in SCORE 2 model. Results: Overall, 589 patients (44.7%) were smokers, mean value of total cholesterol was 6.2±1.1 mmol/L, LDL 3.9±1.1, HDL 1.4±0.5, non HDL 4.8±1.2 mmol/L. Systolic blood pressure was 138.6±19.6, diastolic blood pressure was 85.3±10.4 mmHg and was BMI 26.9±5.2. Based on the SCORE model 166 patients (12.6%) were classified into low risk category, 658 (49.9%) into moderate, 276 (20.9%) into high risk and 217 (16.6%) into very high risk category. Based on the SCORE 2 model 30 (2.8%) patients were classified into low to moderate, 273 (18%) and 1014 (79.2%) into very high risk category. There was significantly less patients in low to moderate group in SCORE 2 model compared to SCORE model (30, 2.8% vs 824, 62.6%, p<0.001 respectively) and significantly more patients with very high risk (1014, 79.2% vs 217, 16.6%, p<0.001), but without significance difference in the high risk group (Figure 1). The use of SCORE 2 model resulted in significantly higher proportion of patients requiring statin treatment 93% vs. 43% using SCORE model (p<0.001). Conclusion: The use SCORE 2 risk prediction tool, in comparison to SCORE model, results in significant higher proportion of patients being classified as very high risk category with the increase number of patients requiring statin treatment in primary prevention. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Krka Farma